Corporate defensive investigation: a study of the Provision 188/2018 of the Brazilian Bar Association’s Federal Council - Anna Carolina Canestraro; Túlio Felippe Xavier Januário (Revista Brasileira de Direito Processual Penal, 2020)
The aim of the present essay is to analyze the Provision 188/2018 of the Brazilian Bar Association’s Federal Council and its possible implications in the corporate internal investigations, which despite their importance, still need regulation. For that we will initially study separately the fundamentals, goals and procedures of defensive and internal investigations, demonstrating that the proximity between these institutes allows us to identify between them a genus-species relationship. From these considerations, we will ascertain in the last topic the possible application of these provisions also to the internal investigations, corroborating the thesis that this regulation is not only applicable to these procedures that are already existent in Brazil, but also represents an important step in the scope of the regulation of their concrete instruments and limits.